Perancangan Standar Operasional Prosedur Logistik Pada PT. Karcia Sentosa Utama - Pratama, Desi; Christiarini, Renny (Pakis Journal Institute, 2024)
Standard Operating Procedure (SOP) is a guide that contains instructions used to ensure the operational activities of an organization or company run smoothly. PT Karcia Sentosa Utama is a company engaged in logistics or freight forwarder with a core part of the business in the form of cross-border cargo and logistics services. PT Karcia Sentosa Utama has legality in running a freight forwarding and cargo service business. All of this is intended so that the business always has the best standards in running a business and serving consumers. The problem experienced by PT Karcia Sentosa Utama is that it does not have a Company SOP so that SOP design and implementation has been carried out at PT Karcia Sentosa Utama. The data collection technique used in this report is to use qualitative research. This qualitative research uses interview, observation and documentation methods. After implementing the company's SOP to PT Karcia Sentosa Utama, it can be analyzed and found that the results of work in the company that the company's conditions have improved in the flow of the company's work system and the work performance of employees in the company, work has become more organized, easy to do, employees are more enthusiastic about working and more focused on work. Based on the results and outcomes achieved for the implementation of the Company's SOP to PT. Karcia Sentosa Utama, there are several suggestions submitted by the author, namely Conducting future observations and monitoring of the implementation of the company's SOP for work at PT. Karcia Sentosa Utama so that it can adjust the SOP & correct errors in the SOP if they occur and training must be carried out for new employees of PT. Karcia Sentosa Utama.